A social network analysis: mental health scales used during the COVID-19 pandemic - Chen, Shuang; Lan, Xue; Yu, Han (Frontiers in Psychiatry, 2023)
The focus on psychological issues during COVID-19 has led to the development of large surveys that involve the use of mental health scales. Numerous mental health measurements are available; choosing the appropriate measurement is crucial. A rule-based named entity recognition was used to recognize entities of mental health scales that occur in the articles from PubMed. The co-occurrence networks of mental health scales and Medical Subject Headings (MeSH) terms were constructed by Gephi. Five types of MeSH terms were filtered, including research objects, research topics, research methods, countries/regions, and factors. Seventy-eight mental health scales were discovered. The findings provide insights on the scales used most often during the pandemic, the key instruments used to measure healthcare workers’ physical and mental health, the scales most often utilized for assessing maternal mental health, the tools used most commonly for assessing older adults’ psychological resilience and loneliness, and new COVID-19 mental health scales. Future studies may use these findings as a guiding reference and compass.